1999
DOI: 10.1097/00002508-199912000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in the Elderly: Occupational Adaptation as a Means of Coping with Osteoarthritis of the Hip and/or Knee

Abstract: This sample of elderly individuals with chronic pain described occupational adaptations, or adaptations to "doing," as a means of coping with their chronic pain. There appeared to be a relation among pain, functional difficulty, depression, social support, and occupational adaptation. Additional research to increase the understanding of occupational adaptation as a means of coping with chronic pain is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 52 publications
5
28
0
1
Order By: Relevance
“…The traditional biomedical view of OA pain is as nociceptive, resulting from joint tissue injury [13]. However, this perspective fails to recognize that pain and other OA symptoms may be strongly influenced by psychological and physical health [40,42], social support [16], gender [43], coping behaviors [27,30,36], and self-efficacy [28]. This explains, in part, why people with similar OA severity radiographically may experience markedly different levels of pain or other symptoms [5,32].…”
Section: Patient Perceptions Of Pain From Oamentioning
confidence: 99%
“…The traditional biomedical view of OA pain is as nociceptive, resulting from joint tissue injury [13]. However, this perspective fails to recognize that pain and other OA symptoms may be strongly influenced by psychological and physical health [40,42], social support [16], gender [43], coping behaviors [27,30,36], and self-efficacy [28]. This explains, in part, why people with similar OA severity radiographically may experience markedly different levels of pain or other symptoms [5,32].…”
Section: Patient Perceptions Of Pain From Oamentioning
confidence: 99%
“…Rest and other interventions such as heat or 'folk' remedies were also used, with medication only taken as a last resort (9,10). Some older people may prefer self-administered strategies for managing their pain (e.g.…”
Section: Impact Of Painmentioning
confidence: 99%
“…Older people with arthritis who maintain engagement in their most valued social and leisure activities are more resilient to depression (Klinger, Spaulding, Polatajko, MacKinnon & Miller, 1999;Payne et al, 2006;Zimmer, Hickey & Searle, 1995). Stevens-Ratchford & Lookingbill (2004) conducted a phenomenological inquiry and found that older people with arthritis described deriving many psychological benefits from their leisure activities.…”
Section: Introductionmentioning
confidence: 99%